Student Interpersonal Communication During Class Presentations (Studies on Student Class of 2022 Communication Studies Program Unyversity of Dehasen Bengkulu) - Yanti, Destia Terida; Narti, Sri; Risdiyanto, Bayu (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
The purpose of this study was to analyze student interpersonal communication during presentations in class (Study on Student Batch 2022 Communication Studies, University of Dehasen Bengkulu). This type of research uses qualitative research methods. The informant's shopping technique uses a snowball sample. There are 3 classes in semester 2, namely A1, A2, A3. Data collection techniques with observation, interview techniques, and documentation studies. Based on the results of the research that has been done, it can be interpreted that of the nine theories, namely the source, the source or the communicator who first opened the presentation in class, it began with students whose clusters served as moderators. Encoding when presenting, the communicator uses Indonesian, sometimes also the semantic regional language, not all students in the class understand what the communicator means. Acceptance of presentations sometimes do not understand what is conveyed by the communicator, if someone does not understand, they can ask the communicator. Channels are used in filtering, communicators are assisted by using laptops in their lighting, some are displaying on the blackboard and using papers and PPT. Decoding all went smoothly communication communication with the communicator. The students' responses understood and understood the material presented. Disturbance (noise), which became a distraction was the noisy sound of the presentation participants which caused distractions and the audience who were busy with their respective cellphones. The context of communication is that communication runs smoothly and well during the presentation.